A Contribution to the History of Publishing in Galicia: Lugo during the Franco Regime - Fernández Pérez-Sanjulián, Carme (Madrygal. Revista de Estudios Gallegos, 2015)
Publication in Galicia during the Franco regime was more prevalent and varied than what is usually believed. This article examines output from publishings in the city of Lugo during the period 1939-1975. The study confirms the range and diversity of initiatives, businesses and individuals involved.